2020
DOI: 10.3390/cells9061564
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenines in the Pathogenesis of Multiple Sclerosis: Therapeutic Perspectives

Abstract: Over the past years, an increasing amount of evidence has emerged in support of the kynurenine pathway’s (KP) pivotal role in the pathogenesis of several neurodegenerative, psychiatric, vascular and autoimmune diseases. Different neuroactive metabolites of the KP are known to exert opposite effects on neurons, some being neuroprotective (e.g., picolinic acid, kynurenic acid, and the cofactor nicotinamide adenine dinucleotide), while others are toxic to neurons (e.g., 3-hydroxykynurenine, quinolinic acid). Not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 294 publications
(364 reference statements)
0
48
0
Order By: Relevance
“…An increasing amount of evidence supports the involvement of kynurenine metabolites and antigen presenting cells expressing IDO1 in neuroinflammatory diseases such as MS ( 13 ). In this study, we found nominally lower levels of KYNA and higher levels of 3HAA in MS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing amount of evidence supports the involvement of kynurenine metabolites and antigen presenting cells expressing IDO1 in neuroinflammatory diseases such as MS ( 13 ). In this study, we found nominally lower levels of KYNA and higher levels of 3HAA in MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other microbiota-related metabolites, such as tryptophan and kynurenine metabolites have been shown to have immunomodulatory properties influencing several inflammatory diseases, including MS. Tryptophan can be metabolized both peripherally and in the CNS into neuroactive kynurenines and aryl hydrocarbon receptor (AHR) ligands that are able to modulate local and distant host functions involving inflammation, neurotransmission and complex immune responses. Gut microbiota are also capable of producing these neuroactive kynurenine metabolites making it interesting in relation to SCFAs ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The kynurenine pathway ( Figure 2 ) is responsible for processing >90% of the Trp in humans, producing kynurenine and niacin as the major metabolites. The build-up of these and other metabolites of this pathway can lead to multiple pathological conditions, such as AIDS-related dementia, multiple sclerosis, and ischemic brain injury [ 46 , 47 , 48 , 49 , 50 ], although the molecular mechanisms are not fully clear.…”
Section: Metabolism Of Trpmentioning
confidence: 99%
“…Perhaps the most enigmatic aspect of Trp metabolism that has defied a clear molecular explanation for years is its intersection with various normal and pathological conditions, such as cancer, multiple sclerosis, transplantation, peripheral and CNS disorders, and recently in SARS-CoV-2 infection [ 47 , 48 , 49 , 50 , 109 , 110 , 111 ]. For the sake of brevity, the focus in this review is on selected branches of immune regulation, a key character in which is indole 2,3-dioxygenase (IDO), the rate-limiting first enzyme in the kynurenine pathway of Trp degradation ( Figure 2 ).…”
Section: Intersection Between Trp Degradation and Immunitymentioning
confidence: 99%
“…In addition to the aforementioned research articles, this Special Issue of Cells also published three review articles that cover different research topics in MS. Forsthuber and colleagues [ 6 ] summarized the role of memory CD4+ T cells in autoimmune diseases, with specific focus on MS and EAE. Vecsei and colleagues [ 7 ] discussed the importance of kynurenines in the pathogenesis of MS. Last but not least, we [ 8 ] provided a comprehensive review on the role of granulocyte-macrophage colony-stimulating factor (GM-CSF) in mediating neuroinflammation, and discussed the potential of targeting GM-CSF in the treatment of MS.…”
mentioning
confidence: 99%